Cultures of Teaching: The Ongoing Commitment to Conservatism - Fockler, Melissa (Critical Education, 2025)
Cultures of teaching represent the habits, knowledge, attitudes, and beliefs that educators share or embody as a professional body or group. To learn more about teaching cultures, specifically cultures of graduate teaching assistants (TAs), I interviewed 17 TAs at a large Canadian university. I adopted Dan Lortie’s classic work on teaching cultures as a theoretical framework and analyzed interviews using grounded theory principles. Results implied that TAs had various teaching habits, including conservative teaching tendencies. According to Lortie, conservatism stands for ways educators rely on their past (schooling) experience to guide how they teach. I build on this, using the phrase ‘Teaching with Ghosts’ to call attention to how an educator’s past experience or prior knowledge, history, and memories haunt classrooms and hinder educational change. While I found evidence of conservatism among TAs, literature indicates that schoolteachers, professors, and teacher candidates for example all have conservative orientations. I conclude with a teaching audit and encourage educators to nurture more sustainable teaching dispositions.